2017
DOI: 10.1186/s13568-017-0356-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sugarcane fiber digestibility, conservation method and concentrate level on the ruminal ecosystem of beef cattle

Abstract: The aim of this study was to investigate the effects of sugarcane neutral detergent fiber digestibility (NDFD), conservation method, and concentrate level on the ruminal microbial population of steers. Eight ruminal-cannulated Nellore steers were distributed in two contemporary 4 × 4 Latin Square design with a 2 × 2 factorial arrangement of treatments. Experiment 1: diets were formulated with 60% of concentrate level, and two sugarcane genotypes (high or low NDFD) either freshly cut or as silage. Experiment 2:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…In our study, the populations of amylolytic bacteria ( R. amylophilus and S. bovis ) increased with increasing starch level. However, De Souza (2017) found that increasing the concentrate in the diets of beef cattle decreased S. bovis abundance and increased R. amylophilus abundance. Others reported that R. amylophilus and S. bovis have a preference for the degradation of NFC and starch ( de Souza et al, 2017 ).…”
Section: Discussionmentioning
confidence: 93%
“…In our study, the populations of amylolytic bacteria ( R. amylophilus and S. bovis ) increased with increasing starch level. However, De Souza (2017) found that increasing the concentrate in the diets of beef cattle decreased S. bovis abundance and increased R. amylophilus abundance. Others reported that R. amylophilus and S. bovis have a preference for the degradation of NFC and starch ( de Souza et al, 2017 ).…”
Section: Discussionmentioning
confidence: 93%
“…For Van Soest (1994), lignin is presented as a limiting factor for fiber degradation, due to the barrier formed making it difficult for microbial adhesion and colonization to break complex bonds. Consequently, the effect of physical replenishment to the rumen environment is highlighted, caused by the indigestible fraction resulting in a reduction in the apparent digestibility of DM, NDF and ADF of the diets with the replacement of sugar cane (Table 3), considering that the lignin-cellulose complex and the crystallinity of this cellulose hinder digestion, characterizing the proportion of indigestible fiber present in the cell wall of sugarcane, which has been evidenced by some authors who have worked with sugarcane in food of ruminants, justifying the low IDM and apparent NDF digestibility coefficient (Cabral et al, 2015, Souza et al, 2017.…”
Section: Discussionmentioning
confidence: 97%
“…Compound samples, classified by animal and experimental period, were formed and later placed in polyethylene containers for further analysis. To estimate the fecal dry matter production, the indigestible acid detergent fiber (iNDF) was used as an internal marker to evaluate feedstuffs, orts and feces using the method described by Valente et al (2011).…”
Section: Use Of Sugar…mentioning
confidence: 99%
“…It is also known that diets with low-quality bulk produce higher amounts of heat and incur higher energy costs in the production process. Thus, one way of diminishing the negative effects of sugarcane fibre quality in the diets of high-production cows would be to increase the use of concentrates, but with caution, as mentioned in the literature (Gonzalez et al ., 2012; Souza et al ., 2017). Another strategy for using sugarcane in the diets of high-production cows would be to mix maize silage (500 : 500 g/kg DM) with the objective of improving the fibre quality of the diet and maximizing the use of maize silage in the herd, in order to maintain the production and quality of milk due to qualitative factors of the roughage (sucrose and starch) used in the diet.…”
Section: Introductionmentioning
confidence: 99%